2022
DOI: 10.1186/s12885-022-10355-3
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemotherapy for patients with international federation of gynecology and obstetrics stages IB3 and IIA2 cervical cancer: a multicenter prospective trial

Abstract: Background Preoperative neoadjuvant chemotherapy (NACT) has been widely used in developing countries for the treatment of patients with International Federation of Gynecology and Obstetrics (FIGO) stages IB3 and IIA2 cervical cancer. However, the effectiveness of NACT and treatment options for NACT-insensitive patients have been concerning. This study will assess prognostic differences between NACT and primary surgery treatment (PST), determine factors associated with prognosis, and explore bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 53 publications
(86 reference statements)
3
11
3
Order By: Relevance
“…It is believed that patients who respond to NACT will benefit from this treatment 16 and studies have been conducted to predict responders in order to obtain survival benefits 17 . However, both our present study and a randomized clinical trial showed that response to NACT does not necessarily mean favorable survival outcomes 15 . The inconsistent correlation between clinical response to NACT and long-term survival implies that future studies should focus on identifying more robust prognostic factors, such as positive lymph node and LVSI after NACT, which were identified as independent risk factors for PFS and OS in our study.…”
Section: Discussioncontrasting
confidence: 52%
“…It is believed that patients who respond to NACT will benefit from this treatment 16 and studies have been conducted to predict responders in order to obtain survival benefits 17 . However, both our present study and a randomized clinical trial showed that response to NACT does not necessarily mean favorable survival outcomes 15 . The inconsistent correlation between clinical response to NACT and long-term survival implies that future studies should focus on identifying more robust prognostic factors, such as positive lymph node and LVSI after NACT, which were identified as independent risk factors for PFS and OS in our study.…”
Section: Discussioncontrasting
confidence: 52%
“…These results suggest that protein levels of HIF-1α and VEGF-A may guide the selection of PCRT and NACT in patients because the reduction is associated with a higher probability of improved clinical responses. However, the predictive value of these markers seems to be limited to LACC because higher protein levels in patients with early-stage cancer correlated with a negative response to treatment with NACT ( 57 , 58 ).…”
Section: Proteins As Predictive Biomarkers In CCmentioning
confidence: 99%
“…For non-metastatic cervical cancer, excluding International Federation of Gynecology and Obstetrics (FIGO) stages IA, IB1, IB2, and IIA1 cancers, concurrent platinum-based chemoradiation is recommended by the National Comprehensive Cancer Network (NCCN) guidelines [ 4 ]. However, clinical applications of these guidelines are limited because of the unavailability of radiotherapy facilities in China [ 5 ]. Concurrent platinum-based chemoradiation has significant adverse effects on reproductive organs during clinical management of cervical cancer [ 6 ], for example, vaginal injuries, ovarian failure, damage to endocrine function, pelvic tissue degeneration, and impaired sexual lifestyle [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Women who received concurrent platinum-based chemoradiation therapies are mostly unable to receive surgical resections because of severe pelvic tissue injuries. Therefore, gynecologists and oncologists want to improve current surgical practices for cervical cancers [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation